ON THE URGENCY TO CHANGE THE METHODOLOGICAL APPROACH TO ENSURE THE ENVIRONMENTAL SAFETY - Вишновецька, Світлана Василівна; Вишновецький, Вадим Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to consider the concept of the environmental safety by analyzing scientific literature and environmental legislation and to justify the urgency to change the methodological approach to its ensuring. Research methods: analysis, synthesis, generalization, comparison, etc. Results: the nature of the environmental safety is generalized and the urgency to change the methodological approach to its ensuring is substantiated. Discussion: the urgency to ensure a balance of economic, environmental and social interests of human and society. To solve the problem of the environmental safety, it is necessary to choose the appropriate methodological approach, which determines the strategy for solving the problem. Since legal regulation should be aimed at ensuring a decent quality of social life, timely and constructive responding the social and natural disasters, global challenges from the world community, taking into account modern innovative trends in socio-economic development of different countries, as well as the whole social, state and personal interests in their balance and interaction, it is necessary to apply the integrated approach. It is concluded that the volume and scale of environmental problems imply the urgency to apply an integrated approach to their understanding and solution to ensure a balance of economic, environmental and social interests of human and society. It is necessary to green all the components of the process of interaction between nature and society. We are talking about an ecological society, ecological entrepreneurship. There is an urgency to form a qualitative environmental management and economic incentive system to reduce the negative impact on the environment. The greening of education as an important area of state activity in the field of educational services, the formation of environmental and legal culture are becoming relevant. The system of legal ensuring the environmental safety needs qualitative development by means of legal and also organizational and administrative, material and technical, methodological means which only in a complex will be able to ensure its coordinated realization. A balance of economic, environmental and social policies is needed.